(untitled) - Webb, Karen (Sydney, 2010)
This second edition has been redesigned and streamlined to ensure effective learning and understanding. It includes new material on social marketing and extensive discussion of the growing role of the internet in all aspects of marketing, as well as updated illustrations and exhibits.
Keywords: Consumer behavior,Marketing